Early Degeneration of Both Dopaminergic and Serotonergic Axons – A Common Mechanism in Parkinson’s Disease - Grosch, Janina; Winkler, Jürgen; Kohl, Zacharias (Frontiers in Cellular Neuroscience, 2016)
Motor symptoms in Parkinson’s disease (PD) are tightly linked to the degeneration of substantia nigra dopaminergic neurons and their projections into the striatum. Moreover, a broad range of non-motor symptoms like anxiety and depression frequently occur in PD, most likely related to the loss of serotonergic neurons and their projections into corresponding targets. Strikingly, nigral dopaminergic neurons and raphe serotonergic neurons are severely affected in PD showing characteristic hallmarks of PD neuropathology, in particular alpha-synuclein containing Lewy bodies and Lewy neurites. So far, the initial events underlying neurodegenerative processes in PD are not well understood. Several observations, however, indicate that neurites and synapses of diseased neurons may be the first subcellular compartments compromised by alpha-synuclein associated pathology. In particular axonal pathology and deficits in axonal transport may be leading to the onset of synucleinopathies such as PD. This review will highlight current findings derived from imaging and neuropathological studies in PD patients, as well as cellular and animal PD models, which define the initial underlying structural and molecular events within dopaminergic and serotonergic circuits leading to the ‘dying back’ degeneration of axonal projections in PD.